A systematic review and meta-analysis of immunohistochemical biomarkers that differentiate chromophobe renal cell carcinoma from renal oncocytoma. Issue 8 (7th March 2016) - Ng, Keng Lim; Morais, Christudas; Bernard, Anne; Saunders, Nicholas; Samaratunga, Hemamali; Gobe, Glenda; Wood, Simon
Abstract : Background: Numerous immunohistochemical (IHC) biomarkers have been employed to aid in the difficult differentiation between chromophobe renal cell carcinoma (chRCC) and renal oncocytoma (RO). A systematic review and meta-analysis of the published literature was carried out to summarise and analyse the evidence for discriminatory IHC biomarkers to differentiate the two entities. Methods: PubMed database was used to identify relevant literature. Primary end point was comparison of positive immunostaining of the biomarkers in chRCC and RO, with extracted data used to calculate OR and 95% CI and statistical I 2 test of heterogeneity for multiple studies. Results: One hundred and nine manuscripts were available for review. Data extracted were subjected to quantitative meta-analysis. Ten most effective biomarkers (OR of chRCC/RO and CI) are: amylase α1A (n=129, OR=0.001, 95% CI 0.0001 to 0.019); Wnt-5a (n=38, OR=0.0076, 95% CI 0.0004 to 0.015); FXYD2 (n=57, OR=130, 95% CI 14.2 to 1192.3); ankyrin-repeated protein with a proline-rich region (ARPP) (n=25, OR=0.0054, 95% CI 0.0002 to 0.12); cluster of differentiation 63 (CD63) (n=62, diffuse (chRCC) vs apical/polar (RO) stain pattern); transforming growth factor β 1 (TGFβ1) (n=34, membranous (chRCC) vs cytoplasmic (RO)); cytokeratin 7 (CK7) (11 studies, n=448, pooled OR=44.22, 95% CI 22.52 to 86.64, I 2 =15%); S100A1 (4 studies, n=124, pooled OR=0.01, 95% CI 0 to 0.03, I 2 =0%); caveolin-1 (2 studies, n=102, pooled OR=32.95, 95% CI 3.67 to 296.1, I 2 =70%) and claudin-7 (3 studies, n=89, pooled OR=24.7, 95% CI 6.28 to 97.1, I 2 =0%). Conclusions: We recommend a panel of IHC biomarkers of amylase α1A, Wnt-5a, FXYD2, ARPP, CD63, TGFβ1, CK7, S100A1, caveolin-1 and claudin-7 to aid in the differentiation of chRCC and RO.